PEMETAAN PERSEBARAN PETERNAKAN KAMBING DI KABUPATEN LIMAPULUH KOTA DENGAN ANALISIS SPASIAL - Cori Qamara; Dwi Yuzaria; Fuad Madarisa (Wahana Peternakan, 2023)
This study aims to locate goat farms in the Limapuluh Kota District. Both primary and secondary data are used. The main information was obtained by answering a questionnaire to count the houses owned by goat farmers and the number of goats. Stratified selection of responders. After that, secondary information was gathered from the Limapuluh Kota Regency's Animal Husbandry and Fisheries Service, Central Agency on Statistic Limapuluh Kota Regency, Regional Planning Agency of Limapuluh Kota Regency, Geospatial Information Agency, and other relevant organizations. ArcGIS version 10.9 was used to conduct the analysis as a spatial analysis using a Geographic Information System (GIS) methodology. The findings show that Limapuluh Kota Regency has 79 districts and 13 sub-districts. There are 6,483 households dedicated to goat breeding and 29,867 goat animals in 77 of the 79 districts, which have goat farms. As a result, it can be concluded that there are goat farms in every subdistrict of Limapuluh Kota Regency. Furthermore, it is clear that the atmosphere in Limapuluh Kota Regency is conducive to goat farming, as evidenced by the fact that goat farms can be found virtually everywhere in the region. It may be said that there is a great deal of room for further development of goat farms. Keywords : Goat Breeders; Goat Population; Spatial Analysis